What’s going on between history and archaeology? – Reflections on reciprocal relationship between two disciplines in historical archaeology in Finland. - Seppänen Liisa (Historiskarkeologiska föreningen, 2022)
Although historical archaeology is established as a specialized field within archaeology in Finland, the relationship between history and archaeology is still questing for a reciprocal alliance. In the first part of the 20th century, historical archaeology was practised mainly by historians and ethnographers who conducted archaeological excavations and combined archaeological findings with historical evidence in their writings and research. Since the 1980s, historical archaeology has experienced a remarkable change and attracted an increasing number of archaeologists with the focus on medieval and post-medieval sites and history. For them combining history with archaeology is self-evident and some of these archaeologists have qualified themselves as historians too. However, historians have not been engaged in historical archaeology and still remain in their studies quite firmly within historical source material. Collaboration between historians and archaeologists does exist to a limited extent and at the individual level, but can we really talk about interdisciplinary co-operation between these two disciplines? Is there any need for such? The article reflects the prevailing situation between these two disciplines in Finland and discusses the reasons for the dominant division and possibilities for a better relationship.